Internet connectivity disruption in Kazakhstan (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Kazakhstan. Data sourced from IODA.
Network Disruption Incident ID: KZ-2026-0052. Severity: critical. Confidence: 65%